Iraq in the Triangle of the Unipolar International System, Terrorism, and Iranian Influence - NORI, SOFIAN SABAH (İstanbul Kültür Üniversitesi, 2023)
This thesis explores the motives and ramifications of the American invasion of Iraq. This thesis seeks to answer the research question, "What are the consequences of the American invasion of Iraq after 2003 on Baghdad and Washington?" Specifically, this study will shed light on the question of to what extent this invasion's decision has been affected by the American purpose of spreading democracy and fighting terrorism as Washington promised or if the U.S. removed Saddam Hussein's regime to emphasize the status quo of the unipolar international system after the Cold War. This study investigates the different elements that have played a significant role in shaping the decision of the invasion and the course after that.

Bu tez, Amerika'nın Irak'ı işgalinin nedenlerini ve sonuçlarını araştırıyor. Bu tez, "2003'ten sonra Amerika'nın Irak'ı işgalinin Bağdat ve Washington üzerindeki sonuçları nelerdir?" sorusuna cevap aramaktadır. Spesifik olarak, bu çalışma, bu işgalin kararında, Washington'un vaat ettiği gibi demokrasiyi yayma ve terörle mücadele amacından ne ölçüde etkilendiği veya ABD'nin tek kutuplu uluslararası statükoyu vurgulamak için Saddam Hüseyin rejimini kaldırıp kaldırdığı sorusuna ışık tutacaktır. Bu çalışma, işgal kararının ve sonrasındaki gidişatın şekillenmesinde önemli rol oynayan farklı unsurları incelemektedir.
▪ Yüksek lisans tezi.
Keywords: Unipolar International System; Terrorism; Iranian Influence